Taxonomia e história evolutiva de Trechaleidae (Aranea: Lycosoidea) - Vinicius Sergio Rodrigues Diniz (2023)
In this thesis, divided in three chapters, I presented a compilation of my studies on trechaleids. Trechaleidae is a family of spiders widely distributed in the Americas, mostly in South, aside from Shinobius orientalis, that occurs in Japan. Many species of the group are called Waterfall Spiders due to their semiaquatic habits. Some of them are also known for giving nuptial gifts, a behavior that invited researchers to carry out reproductive studies within the group. Besides the widely distribution, and the sexual behavior, its evolutionary relationships were hitherto poorly known. In chapter 1 we present the first phylogeny of the family, based in molecular data. Using the obtained phylogenetic tree, we recovered a proximate relationship of Trechaleidae and Lycosidae, although the monophyly of trechaleids has not been corroborated. As a result of the tree, the genera Cupiennius and Neoctenus were nested outside the other members, hence, we propose two new families to relocate those two genera. We present a new circumscription for Trechaleidae, composed by 16 genera, splitted in 3 subfamilies: Shinobiinae, Rhoicininae and Trechaleinae. Shinobiinae is the most basal lineage, and we present evidences for this branch to be categorized as a relictual group. Rhoicininae are composed by Barrisca, Heidrunea and Rhoicinus and Trechaleinae were recovered as a monophyletic group and kept its original conformation. Beyond the phylogenetic work, I presented two taxonomic works in chapters 2 and 3. On chapter 2 we describe a new spider genus, with two new species that occurs only in subterraneous habitats. The two species presents troglomorphic characters, are independent of wate and its distribution are known for karst cavities in Brazil. Finally, on chapter 3 we described a new species of Paratrechalea. Paratrechalea murphyi is known by only one collection record, on a Cerrado biome conservation unit in São Paulo state, an area severely affected by agricultural exploitation. The specimens were collected more than 20 years ago, sampling effort were made in the recorded area, however, we were unsuccessful in finding. On this chapter, we describe the species and discuss its conservation status.